Eficiencia de consorcios microbianos (in vitro) en el tratamiento de aguas residuales domésticas de la ciudad de Calceta - Bravo Álava, Rubén Darío (2016)
This research was carried out in the laboratory of microbiology at ESPAM-MFL polytechnic, located in Calceta, Manabí-Ecuador. It aimed to evaluate the efficiency of microbial consortia (in vitro) in treating domestic wastewater, in Calceta, by means of the DBO5 technique (DBO5 is considered the main indicator of organic matter in wastewater). A complete randomized design with 1 factor and 4 levels (4 treatments) was performed. T1= Bacterial consortium 1,5 ml/〖dm〗^3 application rate formulated with: Saccharomices cerevisiae (4,32*108ucf/ml), Lactobacillus acidophilus (1,848*〖10〗^9 ucf/ml), Bacillus subtilis (7,8*〖10〗^7 ucf/ml). T2= Algae consortium 3 ml/〖dm〗^3 application rate, formulated with: Clorella sp (3,73*〖10〗^6 cel/ml), Clamidomonas sp (4,59*〖10〗^5 cel/ml), Scenedesmus sp (6,2*〖10〗^5 cel/ml). T3= Mixed consortium 3 ml/〖dm〗^3 application rate, formulated with microorganisms of the treatments 1 and 2. T4= Application rates of Fungi consortium (1^8 cel/mg) consisting of Trichoderma harzianun and treatment 1,5 ml/〖dm〗^3 mg/〖dm〗^3. Microbial efficiency was evaluated comparing the reduction rates of organic matter. Mixed consortium (T3) showed the best result with a Biological oxygen demand (BDO) of 21,11 mg/dm3, and 95,15% of organic matter removal; concluding that T3 is the most suitable treatment to be used in domestic wastewater systems due to its high organic matter removal rate.